2018
DOI: 10.1186/s12885-018-4696-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of local tumor control in patients with HCC treated with SBRT or TACE: a propensity score analysis

Abstract: BackgroundAs stereotactic body radiation therapy (SBRT) has shown to be effective and safe in patients with hepatocellular carcinoma (HCC), the aim of our propensity score matched analysis was to evaluate the efficacy of SBRT in comparison to transarterial chemoembolization (TACE) in intermediate and advanced HCC.MethodsPatients treated with TACE (n = 367) and patients allocated to SBRT (n = 35) were enrolled in this study. Propensity score matching was performed to adjust for differences in baseline and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The overall survival at 2 years was 46% versus 53% for SBRT versus RFA, respectively 67. Similarly, after propensity score matching, the LC rate in HCC patients receiving TACE versus SBRT was comparable for local control, overall survival, and 1 year mortality 68…”
Section: Resultsmentioning
confidence: 93%
“…The overall survival at 2 years was 46% versus 53% for SBRT versus RFA, respectively 67. Similarly, after propensity score matching, the LC rate in HCC patients receiving TACE versus SBRT was comparable for local control, overall survival, and 1 year mortality 68…”
Section: Resultsmentioning
confidence: 93%
“…Several, retrospective, studies that used propensity score matching in order to compare both treatments, indicate that SBRT could be an alternative to TACE in terms of local control. Bettinger et al ( 23 ) showed similar local control rates after 1 year (TACE: 82%, SBRT 84.8%, p = 0.8) and OS (TACE: 11 months, SBRT 9 months, p = 0.49) for both treatments, with moderate toxicity, whereas Sapir et al ( 24 ) showed that both LC at 1 year (SBRT 91%, TACE 47%, p < 0.001) and toxicity (TACE: 13%, SBRT: 8%, p = 0.05) favored SBRT, without any difference in the OS. Similarly, in a study by Shen et al ( 25 ) SBRT showed a better in-field control after 3 years (77.5 vs. 55.6%) and OS rates (3-year OS of 55 vs. 13%) than TACE in patients with medium-sized HCC, particularly for recurrent cases.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that SBRT is as effective as local ablation for early stage hepatocellular carcinoma and has similar efficacy to TACE for intermediate stage disease. [103][104][105][106][107] A small, open label, phase II randomized controlled trial showed that SBRT in combination with TACE was superior to sorafenib in improving the survival of patients with advanced stage disease. 108 While SBRT is not currently considered as a first line treatment option for hepatocellular carcinoma, it could be a promising alternative treatment, especially when primary treatment modalities are not feasible.…”
Section: Surgical Resectionmentioning
confidence: 99%
“…It is a highly conformal technique using external beam radiation therapy delivered in high doses to the tumor in a small number of fractions. Multiple studies have shown that SBRT is as effective as local ablation for early stage hepatocellular carcinoma and has similar efficacy to TACE for intermediate stage disease 103104105106107. A small, open label, phase II randomized controlled trial showed that SBRT in combination with TACE was superior to sorafenib in improving the survival of patients with advanced stage disease 108.…”
Section: Treatmentmentioning
confidence: 99%